Ahmad Amin Perspective of As-Sunnah - Atho'illah Umar (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2018)
Moslems faith towards the position and autenthicity of hadits or sunnah in the period of the prophet SAW are unquestioned, because if ever they found anything that brought doubt or unclear they could easily confirm it to the prophet SAW. Contrary to the time after his passing until now, the issues of hadist has been complicated, which lead to opened the veil to see his being as a religious authority. As did by Ahmad Amin in his book Fajr al-Islam, who criticize some things in the hadist. According to him, the originality of the hadist after the passing of the prophet worth to be questioned. This paper trying to observe the thought of Ahmad Amin about Sunnah especially the one associated with the authencity of Sunnah after the passing of Rasulullah SAW and the critics of some ulama on his thought which against the flow of the concept of Sahabat’s honesty which have become the Ijma’ of most Ulama specifically muhaddithin.